2023
DOI: 10.3389/fvets.2022.1046704
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of early immune responses elicited by live and inactivated vaccines against Johne's disease in goats

Abstract: Mycobacterium avium subspecies paratuberculosis (M. paratuberculosis) is the causative agent of Johne's disease, a chronic debilitating condition affecting ruminants causing significant economic losses to the dairy industry. Available inactivated vaccines are not effective in controlling the disease and vaccinated animals can continue to infect newly born calves. Recently, we have shown that a live-attenuated vaccine candidate (pgsN) is protective in goats and calves following challenge with virulent strains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There were no significant differences in the number and distribution pattern of B (CD20+) and T (CD3+) lymphocytes between the groups. A previous study found that at 3 weeks post-vaccination with Mycopar ® , B cells were in moderate numbers, and T cells were scarce, while at 6 months post-vaccination, both were abundant at the periphery of the granulomas ( 66 ). Therefore, it seems feasible that lymphocyte recruitment mainly takes place after the first month of granuloma formation, and they persist for a long period thereafter.…”
Section: Discussionmentioning
confidence: 98%
“…There were no significant differences in the number and distribution pattern of B (CD20+) and T (CD3+) lymphocytes between the groups. A previous study found that at 3 weeks post-vaccination with Mycopar ® , B cells were in moderate numbers, and T cells were scarce, while at 6 months post-vaccination, both were abundant at the periphery of the granulomas ( 66 ). Therefore, it seems feasible that lymphocyte recruitment mainly takes place after the first month of granuloma formation, and they persist for a long period thereafter.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a previous study successfully utilized BALB/c mice to screen a large transposon mutant library [ 21 ]. Some of these mutants were characterized as immunogenic and attenuated in ruminants validating the BALB/c murine model [ 22 , 23 ]. Based on all of these studies, BALB/c mice and their derived cell lines provide a good model that can be correlated with bovine experiments.…”
Section: Introductionmentioning
confidence: 99%